Ureteropelvic Junction Obstruction (UPJO) - Miranda, Monik Ediana; Widjaja, Tommy (Majalah Patologi Indonesia, 2023)
Ureteropelvic junction obstruction (UPJO) is an abnormality in the canal that connects the renal pelvis to the ureter, leading to impairment of urinary flow. The use of maternal ultrasound has increased the number of UPJO during the antenatal period. Histopathological features in UPJO are important for establishing the diagnosis and understanding the pathogenesis of the condition. The current study aims to explain the irregularity of the muscularis propria and a decreased Cajal cells in the affected segment of the UPJO.